2018
DOI: 10.3389/fchem.2018.00212
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Synthesis of Misszrtine A: A Novel Indole Alkaloid From Marine Sponge-Associated Aspergillus sp. SCSIO XWS03F03

Abstract: A novel indole alkaloid, misszrtine A (1), was isolated from marine sponge-derived fungus Aspergillus sp. SCSIO XWS03F03. The planar structure of 1 was assigned by analysis of spectroscopic data, the absolute configuration of which was unambiguously determined by total synthesis. Compound 1 represents the first example of N-isopentenyl tryptophan methyl ester with a phenylpropanoic amide arm, which exhibited a potent antagonistic activity on HL60 (IC50 = 3.1 μM) and LNCaP (IC50 = 4.9 μM) cell lines. Bioactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
(25 reference statements)
0
20
0
Order By: Relevance
“…and was shown to possess potent antibiotic activity against Staphylococcus aureus (MIC = 37 ng/ml) and Enterococcus faecium (MIC = 78 ng/ml), indicating that it could be evaluated further in advanced models of infectious disease (Cueto et al 2001). Another new compound sorbicillactone A isolated from the sponge-derived fungus Penicillium chrysogenum exhibited promising activity against leukemia cells without exhibiting notable cytotoxicity (Zhou et al 2018). This work has been undertaken with the aim of cultivation of the fungus on different medium in shaking and static conditions.…”
Section: Introductionmentioning
confidence: 99%
“…and was shown to possess potent antibiotic activity against Staphylococcus aureus (MIC = 37 ng/ml) and Enterococcus faecium (MIC = 78 ng/ml), indicating that it could be evaluated further in advanced models of infectious disease (Cueto et al 2001). Another new compound sorbicillactone A isolated from the sponge-derived fungus Penicillium chrysogenum exhibited promising activity against leukemia cells without exhibiting notable cytotoxicity (Zhou et al 2018). This work has been undertaken with the aim of cultivation of the fungus on different medium in shaking and static conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Cell cycle progression analyses of 22Rv1 cells that were treated with 12 also revealed discrete G2/M-phase arrest [29]. Compound 18 exhibited potent cytotoxic activity against HL-60 and LNCap cells with IC 50 values of 3.1 and 4.9 µM, respectively, but with no significant cytotoxicity against the rest of the tested cell lines (HepG2, Hela, A375, A549, HT29, SK-BR-3, and MCF-7) [31]. Compounds 20 and 69 exhibited significant inhibitory activities against thioredoxin reductase with IC 50 values of 12.2 ± 0.7 and 13.6 ± 0.6 µM (the IC 50 of the positive control curcumin was 25 µM), but weak toxicity against A549 cells (IC 50 > 10 µM), which suggested that these two compounds might act as microenvironmental regulators of tumor progression and metastasis [33].…”
Section: Biological Activitiesmentioning
confidence: 96%
“…[44], Phakellia fusca [48], Rhabdermia sp. [60], and an unidentified species [31,43], and they accounted for 14.6% of the newly reported heterocyclic alkaloids. Six heterocyclic alkaloids (30 and 92-96) were also isolated from the endophytic fungi (A. sp.…”
Section: Production Environmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Exploration of fungal metabolites is significantly increased after the scientists figured out that marine fungi, especially sponge-associated fungi, produce structurally unique bioactive compounds (Hasan et al 2015;Imhoff 2016). This fungal group produced certain potential bioactive compounds for pharmaceutical application such as citreorosein (anti-obesity activity, IC 50 = 0.17 lM), truncateol M (antiviral activity, IC 50 = 8.8 lM), misszrtine A (cytotoxic, IC 50 = 3.1 lM), and aspergillusene A (antibacterial activity, MIC = 4.3 lM) (Wang et al 2014;Zhao et al 2015;Noinart et al 2017;Zhou et al 2018). Nevertheless, it is noted that most of the bioactive compounds and their producer were isolated from sponges collected from seagrass or coral reef ecosystems.…”
Section: Introductionmentioning
confidence: 99%